PEMBELAJARAN BERDIFERENSIASI PELAJARAN PENDIDIKAN KEWARGANEGARAAN DI SEKOLAH DASAR - Rika Nurbayanti; Herena Yanti Febriyanti; Sofyan Iskandar; Effy Mulyasari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Differentiated learning is an instructional approach based on the understanding that each student has unique needs, interests, abilities, and learning styles. In the context of Civics Education (PKn), this implies that students come from diverse backgrounds, beliefs, and experiences, which can influence how they understand and apply the values of Pancasila and citizenship concepts in their daily lives. This study aims to analyze the effectiveness of differentiated learning in Civics Education for elementary school students. This research employs the Systematic Literature Review (SLR) method, utilizing the Publish or Perish (POP) tool with keywords such as "differentiated learning" and "civics education in elementary schools," limited to the years 2019–2024. From an initial selection of 40 articles, the top 10 were chosen based on the highest citation counts and relevance to the research theme. The findings reveal that differentiated learning in Civics Education at the elementary school level has proven effective in enhancing students' understanding and engagement. This study supports the importance of implementing a differentiated approach in the Merdeka Curriculum, as it provides more meaningful learning experiences for students.